2008
DOI: 10.1104/pp.107.114603
|View full text |Cite
|
Sign up to set email alerts
|

Independence and Interaction of Regions of the INNER NO OUTER Protein in Growth Control during Ovule Development    

Abstract: The outer integument of the Arabidopsis (Arabidopsis thaliana) ovule develops asymmetrically, with growth and cell division occurring primarily along the region of the ovule facing the base of the gynoecium (gynobasal). This process is altered in the mutants inner no outer (ino) and superman (sup), which lead to absent or symmetrical growth of the outer integument, respectively. INO encodes a member of the YABBY family of putative transcription factors, and its expression is restricted to the gynobasal side of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
14
2
1
Order By: Relevance
“…However, our results indicate that despite clear orthology and conserved developmental roles, tomato and Arabidopsis INO proteins are not interchangeable as SlINO could not complement an Arabidopsis ino mutant when expressed from P- AtINO . This is in contrast to similar experiments with other paralogous Arabidopsis YABBY proteins, which promote varying levels of outer integument growth [ 38 , 41 ] despite lower levels of amino acid identity with AtINO (30 % to 35 %) than SlINO shares with AtINO (43 %). This result suggests that there are specific residues required for proper function of AtINO which are missing in SlINO, consistent with prior data that showed important determinants of AtINO function are distributed throughout the protein, rather than in a single structural domain [ 38 , 41 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our results indicate that despite clear orthology and conserved developmental roles, tomato and Arabidopsis INO proteins are not interchangeable as SlINO could not complement an Arabidopsis ino mutant when expressed from P- AtINO . This is in contrast to similar experiments with other paralogous Arabidopsis YABBY proteins, which promote varying levels of outer integument growth [ 38 , 41 ] despite lower levels of amino acid identity with AtINO (30 % to 35 %) than SlINO shares with AtINO (43 %). This result suggests that there are specific residues required for proper function of AtINO which are missing in SlINO, consistent with prior data that showed important determinants of AtINO function are distributed throughout the protein, rather than in a single structural domain [ 38 , 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to similar experiments with other paralogous Arabidopsis YABBY proteins, which promote varying levels of outer integument growth [ 38 , 41 ] despite lower levels of amino acid identity with AtINO (30 % to 35 %) than SlINO shares with AtINO (43 %). This result suggests that there are specific residues required for proper function of AtINO which are missing in SlINO, consistent with prior data that showed important determinants of AtINO function are distributed throughout the protein, rather than in a single structural domain [ 38 , 41 ]. Taken together our results show that failure to complement in a heterologous expression experiment is not a reliable indicator that the proteins have diverged in their biological roles in the plants from which they derive.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some of these interactors correspond to transcription or other regulatory factors potentially involved in different pathways. These include INNER NO OUTER (INO, At1g23420, involved in ovule outer integument development, [61] ), RESPONSE REGULATOR 14 (ARR14, At2g01760, involved in cytokinin signalling, [62] ), ABERRANT LATERAL ROOT FORMATION 14 (ALF4, At5g11030, involved in lateral root development, [63] ) from the Y2H-screen and PPD (involved in leaf development, [35] ), OBERON (OBE) and TITANIA (TTA) (both involved in embryonic root meristem initiation, [42] , [43] ), and SPINDLY (involved in cytokinin and gibberellin signalling, [45] , [64] ) reported here. The obe1 obe2 and tta1 tta2 double mutants are defective in root development [42] , [43] .…”
Section: Discussionmentioning
confidence: 99%
“…In wus (wuschel) ovules both integuments are lacking and there is no normal curvature (Gross-Hardt et al, 2002). In ino (inner no outer), the outer integument is almost lacking (initiated but not further developed) but the inner is well developed, and there is no curvature (Baker et al, 1997;Schneitz et al, 1997;Villanueva et al, 1999;Gallagher and Gasser, 2008;Skinner and Gasser, 2009); the same was found in an ino mutant of the basal angiosperm Annona squamosa (Lora et al, 2011). In pfs2 ( pretty few seeds2) mutants with the PFS2 transgene some ovules are normal; however, in some ovules the outer integument is reduced (shorter than the inner) and the ovule is only halfway curved (Park et al, 2004(Park et al, , 2005.…”
Section: Development Of Curvature In Ovulesmentioning
confidence: 99%